Graphene Oxide Membranes for Tunable Ion Sieving in Acidic Radioactive Waste - Wu, Tong (Adv Sci (Weinh), 2021)
Graphene oxide (GO) membranes with unique nanolayer structure have demonstrated excellent separation capability based on their size‐selective effect, but there are few reports on achieving ion–ion separation, because it is difficult to inhibit the swelling effect of GO nano sheets as well as to precisely control the interlayer spacing d to a specific value between the sizes of different metal ions. Here, selective separation of uranium from acidic radioactive waste containing multication is achieved through a precise dual‐adjustment strategy on d. It is found that GO swelling is greatly restricted in highly acidic solution due to protonation effect. Then the interlayer spacing is further precisely reduced to below the diameter of uranyl ion by increasing the oxidation degree of GO. Sieving uranyl ions from other nuclide ions is successfully realized in pH =3–3 mol L(−1) nitric acid solutions.